2017
DOI: 10.1534/g3.116.038638
|View full text |Cite
|
Sign up to set email alerts
|

A New Reference Genome Assembly for the Microcrustacean Daphnia pulex

Abstract: Comparing genomes of closely related genotypes from populations with distinct demographic histories can help reveal the impact of effective population size on genome evolution. For this purpose, we present a high quality genome assembly of Daphnia pulex (PA42), and compare this with the first sequenced genome of this species (TCO), which was derived from an isolate from a population with .90% reduction in nucleotide diversity. PA42 has numerous similarities to TCO at the gene level, with an average amino acid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
141
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(148 citation statements)
references
References 71 publications
6
141
1
Order By: Relevance
“…We also observed that proteins identified as mutual best BLAST hits between the TCO protein reference used in this analysis and a more recent PA42 D. pulex protein reference are highly enriched among the proteins we were able to detect. Out of 11 697 such proteins, we detected 4312 (expected = 2004), while among the 18 063 proteins with ambiguous hits or no hits, we detected only 786 (expected = 3094; Fisher exact test p < 1 × 10 –248 ).…”
Section: Resultssupporting
confidence: 51%
“…We also observed that proteins identified as mutual best BLAST hits between the TCO protein reference used in this analysis and a more recent PA42 D. pulex protein reference are highly enriched among the proteins we were able to detect. Out of 11 697 such proteins, we detected 4312 (expected = 2004), while among the 18 063 proteins with ambiguous hits or no hits, we detected only 786 (expected = 3094; Fisher exact test p < 1 × 10 –248 ).…”
Section: Resultssupporting
confidence: 51%
“…We also observed that proteins identified as mutual best BLAST hits between the TCO protein reference used in this analysis and a more recent PA42 D.pulex protein reference [24] are highly enriched among the proteins we were able to detect. Out of 11697 such proteins we detected 4312 (expected=2004), while among the 18063 proteins with ambiguous hits or no hits we detected only 786 (expected=3094; Fisher Exact Test P<1E-248).…”
Section: Outcomes Of Ms Analysis and Protein Identificationsupporting
confidence: 52%
“…Although Daphnia pulex genome is relatively well characterized [23,24], the exact number of protein coding genes in the genome is still subject of debate, as it varies significantly between closely related genomes and/or between gene model methodologies [24].…”
Section: Introductionmentioning
confidence: 99%
“…Identifying mRNA targets computationally with miRanda results in many false positives due to the redundancy of the 6–8 bp miRNA‐binding seed sequence (Agarwal, Bell, Nam, & Bartel, ; Peterson et al., ). Of the 116 miRNAs (5p and 3p) we quantified, 4256 potential mRNA targets were identified, an average of 37 per miRNA, a figure possibly further inflated by overaggressive annotation of the D. magna genome (Ye et al., ). Currently, there are 29,128 gene predictions, but this may drop significantly with future resources, as was the case for Daphnia pulex (Colbourne et al., ; Orsini et al., ; Ye et al., ).…”
Section: Resultsmentioning
confidence: 99%
“…Of the 116 miRNAs (5p and 3p) we quantified, 4256 potential mRNA targets were identified, an average of 37 per miRNA, a figure possibly further inflated by overaggressive annotation of the D. magna genome (Ye et al., ). Currently, there are 29,128 gene predictions, but this may drop significantly with future resources, as was the case for Daphnia pulex (Colbourne et al., ; Orsini et al., ; Ye et al., ). Functional characterization of the processes regulated by miRNAs of interest is therefore inaccurate at best.…”
Section: Resultsmentioning
confidence: 99%